Handbook of Coil Winding Technologies for efficient electrical wound products and their automated production - Hagedorn, Jürgen; Sell-Le Blanc, Florian; Fleischer, Jürgen; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer Vieweg, 2018)
This book presents the current coil winding methods, their associated technologies and the associated automation techniques. From the introduction as a forming joining process, over the physical properties of coils, the semifinished products (wire, coil body, insulation) are introduced. In the process chain, different winding methods are used for magnet wire winding. Finally, the automation of these processes is described.
Introduction -- Copper wire -- Winding technology -- Automation.
Keywords: Electric power production; Industrial engineering; Production engineering; Control engineering; Robotics; Automation; Automotive engineering; Electrical Power Engineering; Industrial and Production Engineering; Control, Robotics, Automation; Automotive Engineering